Heterogeneity of Rotavirus Testing and Admitting Practices for Gastroenteritis among 12 Tertiary Care Pediatric Hospitals: Implications for Surveillance - Julie A. Bettinger; Kathryn Wills; Nicole Le Saux; David W Scheifele; Scott A. Halperin; Wendy Vaudry; Members of the Canadian Immunization Monitoring Program, ACTive (IMPACT) (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The Canadian Immunization Monitoring Program, ACTive (IMPACT) surveillance for rotavirus relies on monitoring hospital admissions. Because a diagnosis of rotavirus is not necessary for treatment purposes, and rotavirus is not a reportable disease, wide variation may exist in the admitting and testing practices for this disease. From 2005 to 2007, the number of rotavirus admissions differed significantly among IMPACT centres, and this variation could not be explained by population differences alone. Understanding this variation is important when interpreting surveillance data and estimating the cost-effectiveness of rotavirus vaccination programs.